Antara Efisiensi dan Legitimasi: Dilema Penerapan E-Voting dalam Pemilihan Kepala Desa (Pilkades) dan Sistem Demokrasi di Indonesia - Samuel Joey Elmanta Tarigan; Sayyid Verrel; Ilham Ramadhan; Fatkhuri Fatkhuri; Reja Reja (Indo Publishing, 2026)
The implementation of electronic voting (e-voting) in Indonesian Village Head Elections (Pilkades) presents a fundamental paradox between the promise of technological efficiency and the challenge to democratic legitimacy. This study critically analyzes the extent to which e-voting in the context of Pilkades can achieve procedural efficiency while maintaining or, conversely, undermining the legitimacy of the grassroots democratic system. Utilizing a qualitative approach with document analysis techniques toward regulations, official reports, and previous studies, this research finds that e-voting technically enhances vote counting efficiency by 60–70%, reduces operational costs, and minimizes human error. However, these technical advantages are inversely proportional to the degradation of legitimacy at the substantive level: low digital literacy in rural areas, regional infrastructure disparities, the potential exclusion of vulnerable voters, and the absence of adequate transparency mechanisms create a deficit in public trust toward election outcomes. This study argues that the efficiency-legitimacy dilemma in e-voting Pilkades is not merely a technical issue, but rather a reflection of structural tensions between governance modernization and the depth of participatory democracy. The novelty of this research lies in the construction of the Efficiency-Legitimacy (EL) Framework analytical tool, which integrates e-government theory with democratic legitimacy theory to evaluate the implementation of voting technology at the village level. Recommended policy implications include the implementation of a hybrid voting system and open algorithm audits as a middle ground to reconcile efficiency and legitimacy.